Magic in Augmented Reality - Dias, J.; Batalha, L. (Proc SIACG 2006: 3rd Ibero-American Symposium in Computer Graphics ((14º Encontro Português de Computação Gráfica e XV1 Congreso Espanhol de Informatica Grafica, CEIG), 2006)
In this paper we suggest a new approach for playing the "Magic The Gathering" game. This approach allows the user to perform a set of game moves within this popular card game using a Tangible Augmented Reality (AR) environment. Each move represents a new interaction involving real and virtual worlds. We try to make the game more realistic and interactive, through the usage of a tangible user interface. Therefore, interaction with virtual objects is simple and natural. Magic in AR, consists of a camera, a computer, a video projection screen and a deck of cards to play the game. The original Magic card deck has been changed to include visual tags to be used within an AR system. However, the changes performed in this card deck don t modify the philosophy found within a common "Magic The Gathering" card deck. Consequently, we propose a new paradigm to play the game, keeping the traditional and known elements of the game that are now part of a system that frees our imagination. We describe the system requirements, its architecture, involving the integration of ArTooKit in the Virtools authoring environment, and finally extract conclusions of the system use and usefulness, drawn from usability evaluation.